DIGITAL INTEGRATED MARKETING COMMUNICATION APPOACHES INFLUENCING PURCHASE DECISIONS OF HERBAL TEA PRODUCTS ON TIKTOK - Paowiwat, Chanikarn; Wimoonard, Thanapon (Journal of MCU Phetchaburi Review, 2025)
This study aimed to (1) examine the relationship between digital integrated marketing communication (DIMC) and consumer purchase decision of herbal tea products on the TikTok platform, and (2) investigate the influence of DIMC on consumers’ purchasing behavior. A quantitative research design was employed, using an online questionnaire (Google Forms) to collect data from 400 respondents. The data were analyzed using descriptive statistics and multiple regression analysis. The results revealed that digital integrated marketing communication had a positive correlation with consumers’ purchase decision, explaining 28.2% of the variance (Adj.R² = 0.282, p < 0.01). The factors significantly influencing purchasing decisions were digital advertising, digital sales promotion, digital publicity and public relations, and digital direct marketing. These elements enhanced consumer awareness, trust, and motivation to purchase. The study suggests that herbal tea entrepreneurs should employ creative and health-oriented content, leverage influencers, and implement real-time promotional activities on TikTok to boost sales and strengthen long-term brand loyalty.